Structural phase transition and spin reorientation of LaFeO3 films under epitaxial strain. Issue 102 (24th October 2016) - Mao, A. J.; Tian, H.; Kuang, X. Y.; Jia, J. W.; Chai, J. S.
Abstract : Structural phase transition and spin reorientation of orthoferrites LaFeO3 epitaxially grown along the pseudocubic (001) direction are investigated based on first-principles calculation. Abstract : Structural phase transition and spin reorientation of orthoferrites LaFeO3 epitaxially grown along the pseudocubic (001) direction are investigated based on first-principles calculation. In the process of the LaFeO3 film growth, two phases Pmc 21 (3) and P 4 mm with the larger ferroelectric are obtained. And spin reorientation transition happened which induced by strain from Γ4 to Γ2 about misfit strain 2.28% in c-ePbnm phase. The critical strain for observation of the Γ4 –Γ2 transition in LaFeO3 is very small, which will be a great surprise for experimental worker.